A Brief Review of the Effects of Vitamin D on Multiple Sclerosis - Miclea, Andrei; Bagnoud, Maud; Chan, Andrew; Hoepner, Robert (Frontiers in Immunology, 2020)
Multiple sclerosis (MS) is characterized as an autoimmune disease affecting the central nervous system. It is one of the most common neurological disorders in young adults. Over the past decades, increasing evidence suggested that hypovitaminosis D is a contributing factor to the risk of developing MS. From different risk factors contributing to the development of MS, vitamin D status is of particular interest since it is not only a modifiable risk factor but is also associated with MS disease activity. MS patients with lower serum vitamin D concentrations were shown to have higher disease activity. However, this finding does not demonstrate causality. In this regard, prospective vitamin D supplementation studies missed statistical significance in its primary endpoints but showed promising results in secondary outcome measures or post-hoc analyses. An explanation for missed primary endpoints may be underpowered trials. Besides vitamin D supplementation as a potential add-on to long-term immunotherapeutic treatment, a recent laboratory study of our group pointed towards a beneficial effect of vitamin D to improve the efficacy of glucocorticoids in relapse therapy. In the following article, we will briefly review the effects of vitamin D on MS by outlining its effects on the immune and nervous system and by reviewing the association between vitamin D and MS risk as well as MS disease activity. We will also review the effects of vitamin D supplementation on MS risk and MS disease activity.